2018
DOI: 10.5194/bg-15-5189-2018
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and taxonomic controls of carbon and oxygen stable isotope composition in <i>Sphagnum</i> across broad climatic and geographic ranges

Abstract: Abstract. Rain-fed peatlands are dominated by peat mosses (Sphagnum sp.), which for their growth depend on nutrients, water and CO2 uptake from the atmosphere. As the isotopic composition of carbon (12,13C) and oxygen (16,18O) of these Sphagnum mosses are affected by environmental conditions, Sphagnum tissue accumulated in peat constitutes a potential long-term archive that can be used for climate reconstruction. However, there is inadequate understanding of how isotope values are influenced by environmental c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Warmed plot quadrats were positioned between the OTC wall and the plot collar. The biomass was clipped using sharp scissors at the base of capitulum at 1 cm below the moss surface (Granath et al, 2018).…”
Section: Vegetation Biomass and Coveragementioning
confidence: 99%
“…Warmed plot quadrats were positioned between the OTC wall and the plot collar. The biomass was clipped using sharp scissors at the base of capitulum at 1 cm below the moss surface (Granath et al, 2018).…”
Section: Vegetation Biomass and Coveragementioning
confidence: 99%
“…Sphagnum magellanicum belongs to the subgenus Sphagnum, which is a group of large and stout species with cucullate leaves. Sphagnum magellanicum stands out in its subgenus due to its colour that varies from deep red to almost completely green (Figure 1) collectively in the past, and that they had not been differentiated at the time of data collection, we here follow Granath et al (2018) and treat our study species as S. fuscum coll. and S. magellanicum coll.…”
Section: Study Species and Sampling Designmentioning
confidence: 99%
“…Given that S. beothuk/ S. fuscum and S. medium/S. divinum are sister species and were treated collectively in the past, and that they had not been differentiated at the time of data collection, we here follow Granath et al (2018) and treat our study species as S. fuscum coll. and S. magellanicum coll.…”
Section: Study Species and Sampling Designmentioning
confidence: 99%
“…However, earlier research is scarce and does not find a significant relationship between δ 15 N and the quantity of symbiotically fixed N 2 , Hyodo et al 2013, although near zero δ 15 N values indicated high N 2 uptake across six Sphagnum species (Leppänen et al 2015). In a similar manner, bryophyte tissue δ 13 C can provide insight into relative growth rates and photosynthetic activity of bryophytes (Rice 2000), and it is often used as an indicator of environmental factors, such as moisture and temperature conditions (Rice 2000;Bramley-Alves et al 2015;Granath et al 2018). In bryophytes, C uptake is lower at high water content due to low CO 2 diffusion through water (Rice and Giles 1996;Williams and Flanagan 1996).…”
Section: Introductionmentioning
confidence: 99%